“Bitch”, “Ho” and “Pussy”: Messages of Popular Rap Music - Ahmad Daniel Faiz Ramlee; John, Dexter Sigan (Trends in Undergraduate Research, 2023)
This study aims to examine the messages of the popular rap songs. The specific objectives are: (1) to analyse the messages of rap songs in the Billboard Hot 100 Year-End Chart from 2017 to 2021, and (2) to analyse the level of misogyny in the rap songs listed in the Billboard Hot 100 Year-End Chart from 2017 to 2021. The descriptive study involved the analysis of messages in 25 popular rap songs. The content analysis of the songs showed that the most frequently used type of misogyny is sexual conquest messages found in 23 songs, followed by derogatory manner and physical aggression but rape and sexual assault messages were less frequently used. Most of the songs fall under the high level of misogyny. The most popular words used in these five songs are “bitch”, “hoes”, “ho”, “pussy glitter”, and “whores”. As the rap music is dominated by male singers, the misogyny messages promote a culture of toxic masculinity and reinforce the belief that men should be dominant in all aspects. The rap music normalises the idea of sexual violence, by making it acceptable or even desirable. The findings indicate that there is a need to promote positive messages in the music especially on woman empowerment.